The effect of contact angle on triangular shape interrupted microchannel heat sinks performance - Mohd Azmi, Mohd Irwan; Yeoh, Chit Chuan; Mat Tokit, Ernie; Razali, Nadlene; Abdul Munir, Fudhail; Nordin, Mohd Nur Azmi; Mat Nuri @ Md Din, Nur Rashid (2011)
The effect of different contact angle on triangular shaped interrupted microchannel performance was studied by simulation using FLUENT software. The investigated effects were pressure drop and platinum film temperature. The flow in microchannel is laminar and single phase. Water was used as the working fluid and the interrupted microchannel is made of silicon. A thin platinum film plate was deposited to provide uniform heat flux. The geometry dimension of the heat sink is 30 mm in length, width of 7 mm and the thickness of 0.525 mm. The chosen contact angles that were investigated are 48.13º , 51.27 º and 58.48 º . From the simulation result, pressure drop and thermal dissipation is the highest for contact angle 58.48 º and 48.13 º respectively. Reducing the contact angle reduces the pressure drop and increases the thermal dissipation.